BEYONCE AND BEYOND - Keleta-Mae, Naila. ([S.l.])
1 online resource
Keywords: This book examines three years of Beyonc's career as a pop mega star using critical race, feminist and performance studies methodologies. The book explores how the careful choreography of Beyonc's image, voice and public persona, coupled with her intelligent use of audio and visual mediums, makes her one of the most influential entertainers of the 21st century. Keleta-Mae proposes that 2013 to 2016 was a pivotal period in Beyonc's career and looks at three artistic projects that she created during that time: her self-titled debut visual album Beyonc, her video and live performance of "Formation," and her second visual album Lemonade. By examining the progression of Beyonc's career during this period, and the impact it had culturally and socially, the author demonstrates how Beyonc brought 21st century feminism into the mainstream through layered explorations of female blackness. Ideal for scholars and students of performance in the social and political spheres, and of course fans of Beyonc herself, this book examines the mega superstar's transition into a creator of art that engages with Black culture and Black life with increased thoughtfulness.